Treatment options for reclaiming wastewater produced by the pesticide industry - Goodwin, Lindsey; Carra, Irene; Campo Moreno, Pablo; Soares, Ana (Sciforschen - Open HUB for Science Research, 2017)
The pesticide production industry generates a high strength wastewater containing a range of toxic pollutants (2,4-dichlorphenoxy acetic acid: 2,4-D; 4-(2,4-dichlorphenox) propionic acid: 2,4-DP; 4-(2,4-dichlorophenox) butyric acid: 2,4-DB; 2,4-dichlorophenol: 2,4-DCP; 2,4,6-trichlorophenol: 2,4,6-TCP; 4-chlororthocresol: PCOC; 4-chloro-2-methyl phenoxyacetic acid: MCPA, 4-(4-chloro-2-methylphenoxy) butyric acid: MCPB and 2-(4-chloro-2-methylphenoxy) propionic acid: MCPP). These pesticides can enter the natural environment and water sources if not removed in a wastewater treatment plant. Treated effluents are regulated by legislation such as the Water Framework Directive (WFD). Most studies found in literature focused on synthetic solutions, synthetic wastewater, at lab-scale or pilot-scale. Although these studies can provide information on the removal mechanisms and provide a comparison between process efficiency, they have limited practical applicability. The process that has been more widely used to treat high strength wastewaters rich in recalcitrant compounds at full-scale, is the combination of biological/granular activated carbon and granular activated carbon/biological processes. The pesticide production wastewater contains a variety of compounds, that can be removed by 80-90% using biological processes (such as membrane bioreactors) and granular activated carbon has been shown to selectively remove the pesticides, potentially creating a high quality effluent. Nevertheless, in order to assert processes design, efficiencies or costs, it is crucial to evaluate these processes experimentally.